Edukasi Kesehatan Mental Remaja Pada Siswa Sekolah Menengah Atas Islam Terpadu: Adolescent Mental Health Education For Students Of Integrated Islamic High School - Nuridah, Nuridah; Faikatunnisa, Rika; Khatimah, Husnul; Yodang, Yodang (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Adolescent mental health is a critical issue that directly impacts emotional development, behavior, and academic achievement. High school adolescents are in a transitional phase that is vulnerable to psychosocial stress, anxiety, depression, and trauma, particularly due to academic pressures, social relationships, and developmental changes. Lack of knowledge and awareness about mental health leads to delays in recognizing symptoms and seeking help. This community service activity aims to increase adolescents' knowledge and understanding of mental health concepts, the types, signs, and symptoms of anxiety, depression, and trauma, and to equip students with simple coping strategies for dealing with psychological problems. This activity uses a health education design with a pre-survey baseline approach and counseling intervention. The target group is 18 students at an integrated Islamic high school, with characteristics of adolescent age. The variables measured include levels of anxiety, depression, and psychological trauma. The instruments used in the initial screening were the Generalized Anxiety Disorder-7 (GAD-7) for anxiety, the Patient Health Questionnaire-9 (PHQ-9) for depression, and the PC-PTSD-5/TESI to identify trauma risk. The intervention was carried out through mental health education and the practice of simple coping strategies, such as deep breathing techniques and stress management. Pre-survey results indicated that the majority of students experienced moderate to severe mental health problems. Anxiety levels were predominantly in the moderate (55.6%) and severe (38.9%) categories, while depression was in the moderate (50%) and severe (50%) categories. The risk of psychological trauma was predominantly in the moderate (72.2%) category, followed by severe trauma (22.2%). These findings indicate high mental health vulnerability among high school adolescents and the need for systematic promotive and preventive interventions. This community service activity concluded that mental health education, accompanied by initial screening and training in simple coping strategies, is a relevant and necessary effort to increase adolescents' awareness and ability to manage mental health issues. This program is expected to become a model for sustainable promotive-preventive interventions in school settings to optimally support adolescent mental health.